The effect of reference to the ball on the height of volleyball block jump and volleyball attack jump of volleyball players - Navot, M.; Grosu E. F.; Grosu V. T.; Milo M. (International Scientific Conference eLearning and Software for Education, 2018)
The contribution of this study to the theoretical knowledge is that it compares between volleyball vertical jumps (VJ) without reference to the ball, to volleyball VJ with reference to the ball. This comparison was made possible, for the first time, by the VERT Wearable Jump Monitor (Mayfonk Athletic, Florida, USA), that enables to measure any VJ, anywhere on volleyball court, for up to eight volleyball players at once. This study was conducted at the end of the data collection of the study "The effect of repeated performances of yo-yo intermittent endurance test/run level 1 (YYIE1) preceding to an immediate VJ training, on chronic enhancement of VJ among volleyball players" (intervention program). The study did not find difference between volleyball block jump with or without reference to the ball. However, it found that volleyball attack jump without reference to the ball, was significantly higher than volleyball attack jump with reference to the ball. In addition, the study found that volleyball players that underwent an intervention program for VJ enhancement demonstrated significantly higher volleyball VJ, in all four parameters, than volleyball players that did not undergo this program. The originality of the VJ training in the intervention program was that each volleyball player was required to jump eighty VJs to the maximum height she or he could. This in order to create stimulation for VJ enhancement. The VERT system could supply the data, regarding to VJ height, for the researchers and for each one of the players simultaneously, for up to eight players at once.